Use of Social Media in Small and Medium Enterprises among Adolescents - Adi Rachmanto (Proceeding of International Conference on Business, Economics, Social Sciences, and Humanities, 2023)
The purpose of this research is to find out the effectiveness of small and medium business products marketing through social media and also create work by the needs of society. The method used in this research is a qualitative descriptive approach. The results showed that this method facilitated and accelerated the buying and selling activities for consumers as well as producers and improved the quality of coordination in the marketing team and also increased product sales. Because in the current Era, consumers prefer to buy products with media that are easy to understand as well as liked by consumers. Doing business through social media is very effective and efficient with minimal marketing capital. Product marketing through social media can also make it easier for business owners to do and increase company turnover and expand networks of fellow business and industry partners.